Do Psychiatric Medications Exacerbate Neonatal Withdrawal in Pregnant Women Using Opioid Maintenance Therapy? [27N]. (May 2018) - Ly, Victoria; Persad, Malini D.; Herrera, Kimberly; Garry, David; Garretto, Diana
Abstract : INTRODUCTION: The objective is to determine if opioid maintenance therapy (OMT) in conjunction with psychiatric medications increases the risk of neonatal abstinence syndrome and adverse neonatal outcomes. METHODS: A retrospective cohort study of pregnant women with opioid use disorder was performed at a tertiary care hospital from January 2016 to June 2016. Women were identified from the hospital's delivery logs. Included in the study were pregnant women on opioid maintenance therapy. Women were categorized by whether or not they simultaneously used psychiatric medication or if they did not. Maternal demographics, medical history, social history, maintenance therapy, delivery characteristics and neonatal outcomes were collected from the electronic medical record. A composite adverse neonatal outcome score was created and defined as the presence of any of the following: preterm delivery, birthweight <2500 grams, Apgar score < 7 at 5 minute, NICU admission, and neonatal abstinence syndrome. Data was compared between the two groups with the use of parametric and nonparametric statistics as appropriate. A p value of < 0.05 was considered statistically significant. RESULTS: Of 1, 927 deliveries, 37 women qualified for the study. Compared to pregnant women who used opioid maintenance medications alone, pregnant women who used psychiatric medications were significantly more likely to be nulliparous and have a history of psychiatric disorder. There were no differences in adverse neonatal events, including neonatal abstinence syndrome. CONCLUSION: Using psychiatric medication in conjunction with opioid maintenance therapy has comparable incidence of neonatal abstinence syndrome to using opioid maintenance therapy alone.